SPECTRUM OF TRIGEMINAL NEURALGIA - Rehman, Abdur; Abbas, Iram; Khan, Shahbaz Ali; Ahmed, Ehtisham; Fatima, Fozia; Anwar, Syed Abbas (Journal of Ayub Medical College Abbottabad, 2013)
Background: Trigeminal neuralgia (TN) is a very painful condition characterized by paroxysmal shock like pain in the distribution of one or more branches of trigeminal nerve caused by neuro-vascular conflict at the root entry zone of trigeminal nerve. This study was conducted to analyse the demography and pattern of TN in our setup. Methods: This descriptive study was conducted in the Oral Surgery unit, Department of Dentistry, Ayub Medical College, Abbottabad, from April 2009 to October 2011. A total of 117 patients were included in study by convenience (non probability) sampling technique. All the patients presenting with the clinical features of TN were included in study. Results: Out of 117 cases, 49 (41.9%) were males and remaining 68 (58.1%) were females. Age of the patients ranged from 32-72 (53.90±10.21) years. Right side was involved in 63 patients (53.8%), while the left side was involved in 51 patients (43.6%). In only three cases (2%) there was bilateral involvement. The maxillary division was involved in 68 cases (58.1%) and mandibular division was involved in 37 cases (31.6%). The most common site of involvement was infra-orbital, which was involved in 68 cases (58.11%). The next common site was the mental nerve which showed involvement in 35 cases (29.9%) followed by inferior alveolar nerve which was affected in 14 cases (12%). Thirty three (28.2%) patients were having mild pain, 54 (46.2%) patients having moderate, 21 (18%) patients with severe and 9 (7.7%) patients were having very severe pain. No patient in our study had a family history of TN. Among our patients 103 (88%) patients underwent dental extraction for the same pain. Conclusion: The incidence of TN is more in old age especially in females. TN is frequently misdiagnosed in with tooth ache, so there is need to educate the medical practitioners and masses in order to avoid un-necessary tooth extractions. Keywords: Trigeminal neuralgia, Neuralgia, Trigeminal nerve